The Use of Arabic Children's Songs to Improve Students' Vocabulary Memorization - Muhamad Izzul Arifin; Lina Marlina; Jimmy Surya Nugraha (Gunung Djati Conference Series, 2025)
Mufrodat is an important component in language learning which is the basis for other language skills such as speaking, reading, writing and listening. Children's songs have the characteristics of being easy to remember, fun and entertaining, so they can be an effective medium for improving memorization. This research aims to determine the effectiveness of using Arabic children's song media in improving mastery and memorization of mufradat in class VI MI Ar-rosyidiyah Cibiru, Bandung. The research method used is qualitative. The research subjects were 23 students. Data was collected through mufradat mastery tests before and after implementing classroom action research. The research followed a procedure consisting of four stages, including the planning stage, implementation stage, observation stage and reflection stage, showing that using Arabic children's song media can improve mufradat (vocabulary) memorization for class VI MI Ar-Rosyidiyah students. The results of the research showed that there was a significant increase in students' mastery of mufradat. Apart from that, the use of children's songs in Arabic can also increase students' interest in learning and motivation in learning Arabic. The conclusion of this research is that the use of Arabic children's song media is effective in improving the mastery and memorization of mufradat in class VI students at MI Ar-Rosyidiyah Cibiru, Bandung. It is recommended that the implementation of using Arabic language children's song media be adopted more widely in Arabic language teaching in order to achieve optimal learning outcomes.